Tissue-Specific Metabolic Changes During Postharvest Storage of Friariello Napoletano - Fusco, Giovanna Marta; Annunziata, Maria Grazia; Alberico, Laura; Nicastro, Rosalinda; Woodrow, Pasqualina; Carillo, Petronia (Horticulturae, 2025)
Brassica rapa L. subsp. sylvestris L. Janch. var. esculenta Hort., commonly known as Friariello Napoletano, is a traditional Italian landrace valued for its distinctive flavor, nutritional richness, and cultural relevance in Mediterranean cuisine. The present study investigates the biochemical changes during postharvest storage at two temperatures (4 °C and 10 °C) for 2 and 20 days in its inflorescences and leaves. The experiment aimed to evaluate the evolution of primary and secondary metabolites, with a focus on pigments, amino acids, antioxidants, and glucosinolates. Significant degradation of chlorophylls was observed, particularly in leaves, with reductions of over 90% after 20 days at both temperatures. Conversely, α-tocopherol content increased significantly, especially in inflorescences, indicating an antioxidant response to storage stress. Amino acid analysis revealed a sharp decline in glutamate (up to 79%) and glutamine (up to 83%) in leaves, while proline levels increased across both tissues, reflecting an osmoprotective response. Essential amino acids (EAAs) showed variable responses, with certain EAAs, such as histidine and phenylalanine, accumulating under specific storage conditions. Soluble sugars, starch, and glucosinolates also decreased significantly, with soluble sugars dropping by 87% in inflorescences and 90% in leaves after 20 days at 10 °C. Pathway analysis revealed distinct tissue-specific metabolic responses, with inflorescences exhibiting more stable antioxidant levels and greater resilience to oxidative stress compared to leaves. These findings provide insights into the metabolic adjustments during postharvest senescence and may support future strategies aimed at preserving shelf life and nutritional quality of this traditional Mediterranean vegetable.